A Philosophy of Weakness: Merleau-Ponty on Fugitive Love and the Wisdom in Letting Die. Issue 48 (2nd January 2017) - Whitmoyer, Keith
ABSTRACT: This essay provides a sketch of Merleau-Ponty's understanding of love in relation to human experience and to the conceptualization of φιλία and σοφία outlined in his later works. In response to what he calls a "cruel thought … that is more fear of error than it is a love of truth", Merleau-Ponty's reflections on love and jealousy in Proust offer a concept of "fugitive love". Opposed to the Cartesian desire for apodicticity that seeks to seize and arrest, fugitive love means withholding one's touch and letting the beloved die. In its offer of dispossession rather than possession, love requires faith. This faith, the opposite of faith in an absolute λόγος, invites and accepts being's occultation as the very means of its openness. Merleau-Ponty's thought offers a mode of philosophizing that no longer aims to make being its captive but a philosophy of weakness that allows for its withdraw.